ANALISIS STRATEGI KOMUNIKASI KEMENTERIAN KOMUNIKASI DAN INFORMATIKA REPUBLIK INDONESIA DALAM MEWUJUDKAN ANALOG SWITCH OFF (ASO) DI INDONESIA - Rudito, Yeremia Yori; Prihantoro, Edy (Universitas Gunadarma, 2025)
Analog Switch-Off (ASO) is a process of transition from analog broadcasts system to digital broadcasts system. In the process towards Analog Switch-Off (ASO), it is impossible to be implemented immediately, but it has to be begun by a socialization process from the Ministry of Communication and Information, as the institution in charge of this, to all television industries and the public as users. This is the case that this study tries to examine, namely finding out the communication strategy used by the Ministry of Communication and Information and the internal and external factors that support the implementation communication strategy used by Ministry of Communication and Information. Researchers use the constructivism paradigm, qualitative descriptive method and Rogers' diffusion of innovation theory to analyze. This study produces findings based on research objectives, including the Ministry of Communication and Information socializing Analog Switch-Off (ASO) through various media including television and social media and television has a greater impact. The internal factors include platforms created by the Ministry of Communication and Information to socialize Analog Switch-Off (ASO). The external factor is the regulation of laws governing the implementation of Analog Switch-off (ASO) to stop analog broadcasts so that the migration to digital broadcasts is more convincing to be fully implemented.